Isolation, Assessments of Risk Factors, and Antimicrobial Susceptibility Test of Klebsiella from Gut of Bee in and around Haramaya University Bee Farm, East Hararghe, Oromia Regional State, Ethiopia - Abdallahi Abdurehman Damissie; Kedir Abdurahman Musa (Veterinary Medicine International)
A cross-sectional study was employed from March 2021 to October 2021 to isolate and identify Klebsiella species found in the gut of honey bees collected from worker of honey bee (Apis mellifera) from hives in Haramaya University bee farm, Damota and Finqile’s, managed under traditional and modern beekeeping apiculture. From the selected farm, a total of 60 samples of live adult honey bees were collected purposively. The live adult worker of the honey bee was individually surface-sterilized and complete alimentary canals of the worker bee were dissected and processed for Klebsiella isolation. Descriptive statistics were used to describe the occurrence of Klebsiella species and the proportion of Klebsiella found in the gut was analyzed for the association with study variables by the Pearson chi-square test. The overall prevalence of Klebsiella spp. was 50% from samples. The prevalence of Klebsiella pneumoniae was 26.7% and that of Klebsiella oxytoca was 23.3% from isolated using bacteriological examined samples. The isolates were characterized for the antimicrobial susceptibility test using the disc diffusion method. Among the isolated colonies, Klebsiella pneumoniae had the highest resistance to ampicillin (84.2%) and showed less resistance to gentamycin and trimethoprim sulfamethoxazole (26.3%). Klebsiella oxytoca was highly resistant to ampicillin (54.5%) and erythromycin (54.5%) and showed low and equal resistance to gentamycin and amoxicillin (18.2%). Molecular characterization should be conducted to identify Klebsiella spp. from honey bees. Monitoring antimicrobial effectiveness is recommended to tackle the existing problem in apiculture farms, and its possible public health threat should be noted for community by public health professionals.